Interfirm Bundling and Vertical Product Differentiation1. (23rd June 2014) - Brito, Duarte; Vasconcelos, Helder
Abstract In this paper, we study the competitive effects of bundled discounts offered by pairs of independent firms. In a setting with vertically differentiated goods, where firms decide whether to participate in a discounting scheme before prices are set, it is shown that, in equilibrium, all pairs of firms producing goods of the same quality level offer bundled discounts. Relative to the no‐bundling benchmark, we find that (i) all headline prices rise, (ii) all bundle prices, net of the respective discount, decrease, and (iii) only high‐quality sellers will obtain higher profits. Furthermore, this equilibrium corresponds to the worst scenario in terms of consumer welfare, and it and decreases social welfare.